Influence of Acid Activation of a Mixture of Illite, Koalinite, and Chlorite Clays on the Adsorption of Methyl Violet 6B Dye - Saed, Saba Adel; AL-Mammar, Dunya Edan (Iraqi Journal of Science, 2021)
The influence of acid activation of a mixture of illite, kaolinite, and chlorite clays collected from the area of Zorbatiya (east of Iraq) on the adsorption of methyl violet 6B (MV6B) as a cationic dye was studied. The activation was carried out by using 0.25M HCl and 0.25M . Raw and acid-activated clays were analyzed by atomic force microscopy (AFM), scanning electron microscopy (SEM), and X-ray diffraction (XRD). Batch adsorption method was used to study the adsorption of MV6B onto the raw and acid activated clays. The impacts of different factors on the adsorption process were studied, such as clay weight, agitation time, starting MV6B concentration, temperature, ionic strength, and solution pH. The adsorption process was described by using Langmuir, Freundlich, Temkin, and Dubinin- Radushkevich isotherm models. Thermodynamic parameters like were estimated based on Vanʼt Hoff equation.